PENGARUH GOOD CORPORATE GOVERNANCE (GCG) TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF: (Studi Kasus Empiris pada Bursa Efek Indonesia priode 2016 – 2018) - Refni Melvi Yona; Helmiati Helmiati (Jurnal Riset Manajemen Indonesia, 2020)
This research was conducted with the aim to examine the effect of good corporate governance on earnings management in automotive sub sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The population in this study were all automotive sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018, as many as 13 companies. The technique used in sampling is purposive sampling method, the samples in this study were selected as many as 11 companies. Hypothesis testing uses multiple linear regression analysis with the help of SPSS 23.00 for windows. The results showed that simultaneous institutional ownership, the size of the board of commissioners, the proportion of independent boards of commissioners, and the audit committee affected earnings management. Partially, institutional ownership, the proportion of independent board of commissioners, and the audit committee has an influence on earnings management.